THE EFFECTS OF LEADERSHIP AND MOTIVATION AGAINSTS WORK DISCIPLINE AND PERFORMANCE OF CIVIL SERVANT EMPLOYEES AT BALAI WILAYAH SUNGAI BALI PENIDA - Bayu Permadi; I. B. A Dharmanegara; Ni Wayan Sitiari (Jurnal Ekonomi dan Bisnis Jagaditha, 2018)
This research was conducted at Balai Wilayah Sungai Bali Penida which aims to analyze and explain the influence of leadership and motivation on work discipline and performance of civil servants. The population in this research is all civil servants at Balai Sungai Bali Penida which amounts to 180 people with the sample is 64 civil servants. The research data is primary data obtained from questionnaires to find out the respondent's perception about the variables studied and secondary data obtained from books, references, documents and other information available at Balai Sungai Bali Penida. Testing research hypothesis used Partial Least Square (PLS) application. The results showed that: (1) leadership has a positive and significant effect on work discipline. (2) motivation has a positive and significant effect on work discipline. (3) leadership has positive and insignificant effect on performance. (4) motivation have positive and significant effect to performance. (5) work discipline has a positive and significant impact on performance. (6) the discipline of full mediation between leadership to performance and (7) the discipline of work mediates some of the motivations for the performance of civil servants in the Balai Wilayah Sungai Bali Penida.